Self-perceived oral health status and cytomorphological changes in individuals with addictive oral habits: assessed by WHO oral health questionnaire for adults - Gul, Hamna; Asif, Farhana; Samad, Afra; Minhas, Sadia; Anwar, Malik Adeel; Tayyab, Muhammad Arslan; Kashif, Muhammad (International Journal Of Community Medicine And Public Health, 2017)
Background: Oral diseases related to tobacco use are relatively widespread and common in the Pakistani community but epidemiological data regarding maintenance of oral hygiene and suggested treatment is scarce. Therefore, this study was conducted in an under developed district (Muzaffargarh) of Punjab, Pakistan to evaluate oral health status and to determine frequency of cytomorphological changes in buccal mucosa of habitual tobacco users. Methods: Oral examination of all the subjects was carried out using mouth mirrors and gauze under good illumination. Cytology samples were taken from buccal mucosa. The smears were later stained with Papanicolaou stain and microscopy was performed. All the cytological data was recorded in the respective proformas. Data was analysed using IBM SPSS software version 20. Descriptive statistical analysis was performed. A p value of ≤0.05 was considered significant. Results: When cross relations were studied among the demographics, addictive habits and cytological variables, soft drink usage was associated with epithelial atypia (p=0.05), marijuana usage was associated with inflammatory infiltrate on cytology (p=0.047) and snuff/niswar usage was associated with inflammatory atypia (p=0.048). No associations were found among the other studied variables. Conclusions: The results of cellular changes in the smears from subjects with addictive habits can be utilized as an educational and screening tool in cessation therapy. The results attained in this study proposed that tobacco addictive habits produce cellular modifications in clinically normal mucosa on exfoliation cytology.